Impacts of lost fishing nets in the U.S. portion of the Salish Sea. (February 2023) - Drinkwin, Joan; Antonelis, Kyle; Heller-Shipley, Madison; Rudell, Paul; Etnier, Michael; Good, Tom; Elz, Anna; Morgan, Jason
Abstract: The negative impact of lost (or derelict) gillnets on marine species and habitats has been reported for decades in the U.S. portion of the Salish Sea. Impacts of derelict nets are recognized as stressors to taxa listed under the U.S. Endangered Species Act (ESA), including rockfish and marbled murrelet. This study reports results from a concerted effort to remove derelict nets from the marine environment conducted using diver retrieval methods from 2002 through 2021. Also reported are results from a Reporting, Response, and Retrieval (RRR) Program designed to retrieve newly lost nets that was implemented in 2012. A total of 5638 unique derelict nets or portions of nets was removed. Nets measured a total of 11.6 km 2 . The majority of nets were recovered from habitats of boulders on sand/mud/gravel, followed by low-relief rocky substrate, and high-relief rocky substrate. Age, water depth, and suspension in the water column are reported for all nets removed. A total of 126, 308 individual species impacts representing 119 unique species were documented including commercially and recreationally harvested species. The RRR Program has received 124 reports since 2012 and has proved effective at reducing re-accumulation and long-term species and habitat impacts from lost fishing nets. Recommendations to increase its effectiveness include continued outreach to fishers to encourage compliance with the mandated reporting coupled with increased penalties for not reporting. Systematic retrieval of derelict nets coupled with a program to rapidly retrieve newly lost nets could serve as a model for other coastal net fisheries. Highlights: Strategic removal of derelict fishing nets protects habitat and hundreds of unique species from mortality. Rapid reporting and retrieval of newly lost fishing nets prevents species entanglement and habitat damage. Newly lost fishing nets rapid response program prevents accumulation of nets in the U.S. portion of the Salish Sea. Newly lost fishing nets mandatory reporting and rapid response is an effective fisheries management strategy.